Ewolucja form strategii przedsiębiorstw branży mięsnej - Wołoczek, Przemysław (The Evolution of Forms of Strategies of the Meat Industry Enterprises, 2008)
In this paper the author presents some results of his research about the evolution of forms of strategies of the Polish meat industry enterprises after Poland's accession to the European Union. Great deal of this material refers to characteristics of basic elements of strategy, such as: mission, strategic goals, strategy time-horizon.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 20, s. 429-437